From measuring to managing: The experience of food safety in Vietnam - Nguyen, Hung (2017)
Presentation by Hung Nguyen, Food Safety Workshop 24 May 2017. This was presented at the workshop "Better Targeting Food Safety Investments in Low and Middle Income Countries," hosted by A4NH and LSHTM.